Authentication device and film
Patent Information
- Application Number
- JP2024218343
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-03-28
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0011】 本発明に依れば、フィルムの配向角に認証性が依存することのない認証デバイスを提供できる。また、安価なフィルムを用いることができ、光源の耐久性および画面の耐衝撃性を向上させることができる。
Smart Images

Figure 2025031740000005 
Figure 2025031740000006 
Figure 2025031740000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an authentication device having a light source, a polarizer, a film, and a light-sensitive sensor. [Background technology]
[0002] With the recent development of image processing and data analysis technologies, various authentication systems have been put into practical use. In particular, biometric authentication devices such as fingerprint, iris, vein, and face authentication have become more accurate and less expensive, and are beginning to be used in various electronic products such as mobile phones and vehicles. As these devices are expected to be used more in vehicles and electronic payments in the future, there is a demand for authentication devices that are more accurate, less expensive, and durable enough for long-term use.
[0003] As shown in Patent Document 1, optical authentication devices generally irradiate light emitted from a light source onto an object to be authenticated, receive the reflected light with a light-sensitive sensor, capture an image, and perform authentication by matching the patterned image with a pre-registered pattern. In such authentication devices, if light other than that emitted from the light source enters the device, it can cause erroneous authentication, so polarizers are often used to suppress reflection of external light. In addition, a thermoplastic resin film such as polyester or polycarbonate is used as the outermost layer to prevent deterioration of the authentication function due to breakage or scratches. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2017 / 126153 Summary of the Invention [Problem to be solved by the invention]
[0005] However, if the film has polarizing or optically rotatory properties, the light from the light source will be polarized / rotated, and the polarized / rotated light will be blocked by the polarizer before reaching the light sensitivity sensor, resulting in a problem of reduced authentication.
[0006] There are two possible solutions to this problem. The first is to use an unstretched or slightly stretched film of optically nearly isotropic polycarbonate or the like as a protective film. However, films with low stretch ratios are prone to cracking and have poor impact resistance. In addition, polycarbonate films with high impact resistance have the problem of being expensive.
[0007] The second method is to use an oriented polyester film as a protective film and align the main orientation axis of the oriented polyester film parallel to the transmission axis of the polarizer, thereby substantially eliminating the polarization in the protective film. However, this method has a problem that the polarization becomes apparent when the direction of the main orientation axis and the transmission axis of the polarizer are misaligned by just a few degrees, resulting in a decrease in authentication ability.
[0008] Furthermore, in authentication devices that use OLEDs (Organic Light Emitting Diodes) as the light source, degradation of the OLED due to ultraviolet rays and other factors is an obstacle to long-term use, and improving the durability of OLEDs is a challenge that is directly linked to extending the service life of authentication devices.
[0009] The present invention is intended to solve the above problems, and has an object to provide an authentication device whose authenticity does not depend on the orientation angle of the film. [Means for solving the problem]
[0010] The present invention aims to solve the above problems. That is, the present invention provides an authentication device having a light source, a polarizer, a film, and a light sensitivity sensor, the film being disposed between the polarizer and an object to be authenticated, and satisfying the following (1) and (2). (1) The transmittance of the light beam emitted from the light source is 70% or more and 100% or less at the wavelength at which the light beam has the strongest intensity. (2) There exists an integer n that satisfies the following equation (I): (I)A×n-150 ≦ Re ≦ A×n+150 Here, A is the wavelength (nm) at which the light emitted from the light source exhibits the strongest intensity, and Re is the in-plane retardation (nm) when the film is measured at a wavelength of 587.8 nm and an incident angle of 0° using the parallel Nicol rotation method. Effect of the Invention
[0011] According to the present invention, it is possible to provide an authentication device whose authenticity does not depend on the orientation angle of the film. In addition, it is possible to use an inexpensive film, and it is possible to improve the durability of the light source and the impact resistance of the screen. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a diagram illustrating an example of a configuration of an authentication device according to the present invention. [Diagram 2] 1A to 1C are diagrams illustrating an example of the movement of light used for authentication in the authentication device of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention should not be construed as being limited to the embodiments including the following examples, and various modifications are naturally possible within the scope of the invention that can achieve the object of the invention and does not deviate from the gist of the invention.
[0014] The authentication device of the present invention is an authentication device having a light source, a polarizer, a film, and a light sensitivity sensor, in which a film that satisfies the following (1) and (2) is placed between the polarizer and the object to be authenticated. (1) The film has a transmittance of 70% or more and 100% or less at the wavelength having the strongest intensity of the light emitted from the light source. (2) The following formula (I') is satisfied when the wavelength at which the light emitted from the light source has the strongest intensity is A (nm) and the in-plane retardation at a wavelength of 587.8 nm at an incident angle of 0° of the film measured by the parallel Nicol rotation method is Re (nm). (I´)A×n-150 ≦ Re < A×n+150 Here, n is an integer.
[0015] More specifically, the authentication device of the present invention is an authentication device having a light source, a polarizer, a film, and a light sensitivity sensor, wherein the film is positioned between the polarizer and the object to be authenticated, and is characterized in that it satisfies the following (1) and (2). (1) The transmittance of the light beam emitted from the light source is 70% or more and 100% or less at the wavelength at which the light beam has the strongest intensity. (2) There exists an integer n that satisfies the following equation (I): (I)A×n-150 ≦ Re ≦ A×n+150 Here, A is the wavelength (nm) at which the light emitted from the light source exhibits the strongest intensity, and Re is the in-plane retardation (nm) when the film is measured at a wavelength of 587.8 nm and an incident angle of 0° using the parallel Nicol rotation method.
[0016] The authentication device of the present invention comprises a light source (1), a polarizer (2), a film (3), and a photosensitivity sensor (4) as shown in Figure 1. The light source, polarizer, and film are preferably arranged in this order. The configuration of these components will be described below.
[0017] <light source> The type of light source constituting the authentication device of the present invention can be any light source that emits light in a wavelength region detectable by a light sensitivity sensor. For example, any light source can be used, such as a hot cathode tube, a cold cathode tube, a fluorescent light source such as an inorganic EL, an organic electroluminescence element light source (organic EL), a light emitting diode (LED), or an incandescent light source. In particular, an organic EL or LED is a suitable light source. As described later, it is important to adjust the in-plane phase difference of the film to an approximately integer multiple of the wavelength at which the light emitted from the light source has the strongest intensity (the wavelength at which the light emitted from the light source has the strongest intensity may be referred to as the light source wavelength) in order to improve the authenticity. Since the more light with a wavelength farther away from an approximately divisor of the in-plane phase difference of the film leads to a decrease in authenticity, it is preferable to use a light source with a narrow emission wavelength band and an adjustable emission wavelength. The half-width of the peak at which the light emitted from the light source has the strongest intensity is preferably 5 nm or more and 150 nm or less. It is more preferable that it is 5 nm or more and 70 nm or less. It is particularly preferable that it is 5 nm or more and 50 nm or less. The narrower the wavelength band is and the closer it is to an integral multiple of the in-plane retardation of the film, the more the film's orientation angle dependency, which affects the authentication performance, can be suppressed. The orientation angle here refers to the angle between the transmission axis of the polarizer and the main orientation axis of the film. In the present invention, the main orientation axis of the film represents the direction of the slow axis determined by the measurement method described below. In addition, when the authentication device is installed on the surface of a curved display or the like, a flexible organic electroluminescence (EL) can be preferably used.
[0018] When an organic electroluminescence (EL) light source is used, it is particularly preferable to adopt a structure that blocks ultraviolet rays, as described below. By blocking ultraviolet rays, it is possible to incorporate the advantages of organic electroluminescence (EL), such as flexibility, while compensating for the disadvantage of organic electroluminescence (EL), which is susceptible to ultraviolet degradation.
[0019] The light source may have one type of emission peak or two or more types of emission peaks, but in order to improve color purity, it is preferable to use a light source having one type of emission peak. In addition, it is preferable to use a combination of multiple light sources having different types of emission peaks in order to improve security. When multiple light sources are used, it is preferable to use a film suitable for each light source (the in-plane retardation is approximately an integer multiple of the light source wavelength).
[0020] <Light sensitivity sensor> The authentication device of the present invention needs to be configured to include a light-sensitive sensor to recognize light reflected from an object. Examples of light-sensitive sensors include a Charge-Coupled Device (CCD) and a Complementary Metal-Oxide-Semiconductor (CMOS). Among them, it is preferable to use a CMOS (including Live MOS, back-illuminated CMOS, stacked CMOS, curved CMOS, organic thin-film CMOS, Foveon, etc.) from the viewpoints of manufacturing cost and readout speed. In particular, by combining an organic thin-film CMOS with ultraviolet light shielding, which will be described later, it is possible to obtain an organic thin-film CMOS such as a thin film, while compensating for the drawback of the organic thin-film CMOS being susceptible to ultraviolet light degradation.
[0021] Polarizer The authentication device of the present invention needs to be configured to include a polarizer in order to prevent erroneous authentication due to the incidence of external light. External light here refers to light other than light emitted from a light source that is incident on the light-sensitive sensor side from the film. The material of the polarizer can be selected arbitrarily, but for example, it can be formed by dyeing a polyvinyl alcohol (PVA) film with a dichroic material such as an iodine compound and performing a stretching process. As an example of the PVA film, VF-PS#7500 manufactured by Kuraray can be used.
[0022] <film> The authentication device of the present invention must be configured to include a film. The film must have a transmittance (light source light transmittance) of 70% or more and 100% or less at the wavelength with the strongest intensity of the light emitted from the light source. If the transmittance is less than 70%, the light may not reach the light sensitivity sensor sufficiently, resulting in a decrease in authenticity. More preferably, the transmittance is 80% or more and 100% or less.
[0023] In addition, in the authentication device of the present invention, when the wavelength (light source wavelength) showing the strongest intensity in the light beam emitted from the light source is A (nm) and the in-plane phase difference of the film at a wavelength of 587.8 nm at an incident angle of 0° measured by the parallel Nicol rotation method is Re (nm), it is necessary to satisfy formula (I'). (I´)A×n-150 ≦ Re < A×n+150 Here, n is an integer.
[0024] More specifically, the authentication device of the present invention is an authentication device having a light source, a polarizer, a film, and a light sensitivity sensor, wherein the film is positioned between the polarizer and the object to be authenticated, and is characterized in that it satisfies the following (1) and (2). (1) The transmittance of the light beam emitted from the light source is 70% or more and 100% or less at the wavelength at which the light beam has the strongest intensity. (2) There exists an integer n that satisfies the following equation (I): (I)A×n-150 ≦ Re ≦ A×n+150 Here, A is the wavelength (nm) at which the light emitted from the light source exhibits the strongest intensity, and Re is the in-plane retardation (nm) when the film is measured at a wavelength of 587.8 nm and an incident angle of 0° using the parallel Nicol rotation method.
[0025] Formula (I) indicates that the in-plane retardation of the film is approximately an integer multiple of the light source wavelength (in the range of an integer multiple to ±150 nm). The in-plane retardation of the film is preferably in the range of an integer multiple of the light source wavelength to ±120 nm, and more preferably in the range of ±100 nm. If the in-plane retardation of the film is not within the above range, the light emitted from the light source is polarized when it passes through the film, so that the influence of light absorption by the polarizer becomes large, and the deterioration of the authentication becomes a problem. The degree of polarization depends on the orientation angle. In addition, from the viewpoint of widening the process window, the in-plane retardation is preferably 400 nm or more, more preferably 600 nm or more, and even more preferably 800 nm or more. In addition, as described later, one of the means for adjusting the in-plane retardation is adjusting the stretching ratio, but from the viewpoint of improving the strength of the film, it is not preferable to strongly stretch only in one direction, so that the in-plane retardation is preferably less than 3000 nm. Since the in-plane retardation is greatly affected by the film thickness, if the film thickness is too thick, it is difficult to prepare a film with an in-plane retardation of less than 3000 nm, and similarly, if the film thickness is too thin, it is difficult to prepare a film with an in-plane retardation of 400 nm or more. In order to set the in-plane retardation within the above-mentioned preferred range, it is preferable to set the thickness to 10 μm or more and less than 100 μm from the viewpoint of ease of in-plane retardation adjustment. It is more preferable to set the thickness to 15 μm or more and less than 50 μm.
[0026] It is also possible to improve the authenticity by reducing the stretching ratio to bring the in-plane retardation closer to 0, but this is not preferable from the viewpoint of impact resistance since the film becomes brittle.
[0027] It is most preferable to measure the in-plane retardation at the light source wavelength, but the measurement is performed at 587.8 nm due to the stability of the light intensity of the measurement device. It is preferable that the difference between the in-plane retardation at the light source wavelength and the in-plane retardation at a wavelength measurable by the measurement device is 40 nm or less.
[0028] The mechanism by which light absorption by the polarizer increases when the in-plane retardation is not within the above range will be described. When authenticating an object to be authenticated using the authentication device of the present invention, light emitted from a light source passes through a polarizer and then a film before reaching the object to be authenticated, and the light reflected by the object to be authenticated passes through the film and then a polarizer, and is detected by a light sensitivity sensor. The light path is shown by arrows in Figure 2.
[0029] A polarizer absorbs light with a specific polarization state and transmits only light with other polarization states. Therefore, when light emitted from a light source passes through a polarizer, it becomes linearly polarized or circularly polarized. If the film is not polarized (optically isotropic), the polarization state of the light emitted from the light source, passing through the polarizer and entering the film, and the light reflected by the object to be authenticated and entering the film, does not change before and after passing through the film. Therefore, if the film is not polarized (optically isotropic), the polarization state does not change when the light is emitted from the light source and passes through the polarizer, and when it passes through the film, and when it is reflected by the object to be authenticated and passes through the film and enters the polarizer, so it passes through the polarizer without being absorbed and is recognized by the light sensitivity sensor.
[0030] However, if the film is polarized, the light emitted from the light source and passing through the polarizer changes its polarization state when passing through the film and when passing through the film after being reflected by the object to be authenticated. As a result, some of the light is absorbed by the polarizer and cannot pass through. This reduces the intensity of the light that reaches the light sensitivity sensor, leading to a decrease in authentication. The polarization of the film is caused by the difference in optical path length between the main orientation axis direction and the direction perpendicular to the main orientation axis, that is, the in-plane phase difference. The phase of the two lights is shifted and polarized when the light vibrating in the main orientation axis direction is faster or slower than the light vibrating in the perpendicular direction.
[0031] On the other hand, in the authentication device of the present invention, the in-plane phase difference is set to an approximate integer multiple of the light source wavelength, so that the phase shift is set to an approximate integer multiple of 2π, and the phase shift is essentially close to zero. If the phase shift is small, the decrease in the intensity of light after passing through the polarizer can be suppressed even if the orientation angle is shifted. Therefore, if the in-plane phase difference of the film is within the range of the above formula (I), the decrease in authenticity can be suppressed.
[0032] For example, when the light source wavelength is 525 nm, it was found that when the in-plane retardation is an integer multiple of 525 nm, high transmittance is obtained regardless of the orientation angle. Authentication performance was also confirmed using the method described below, and it was confirmed that if the authenticity is A or B by adjusting the in-plane retardation, it shows good authentication performance for use as a screen protector for smartphones with in-screen fingerprint authentication. Examples of smartphone models include Vivo's X20 Plus UD, X21, and NEX.
[0033] Furthermore, when there are multiple light sources of different colors and it is desired that all of the colors be received by the photosensitivity sensor, it is preferable to use a film that has an in-plane retardation that is an integer multiple of the wavelength of the second strongest light emitted from the light source.
[0034] In other words, when the wavelength exhibiting the second strongest intensity among the light rays emitted from the light source is B (nm) and the in-plane retardation when the film is measured at a wavelength of 587.8 nm at an incident angle of 0° using the parallel Nicol rotation method is Re (nm), it is preferable that there exists an integer m that satisfies the following formula (II): (II) B×m-150 ≦ Re ≦ B×m+150.
[0035] The "wavelength showing the second strongest intensity" here is selected from the wavelength that is the peak when the wavelength dependency of the light intensity of each light source is plotted. The "peak" here refers to the wavelength that is the maximum value when the wavelength dependency of the emission intensity of the light is plotted. The "maximum value" here refers to the wavelength where the sign changes from positive to negative when the light intensity is differentiated with respect to the wavelength. When there is only one light source, among the peak wavelengths, the wavelength that is the second strongest after the "wavelength showing the strongest intensity (A)" and does not fall under the following two points is designated as the "wavelength showing the second strongest intensity (B)." Here, the intensity of A is designated as P(A) and the intensity of B is designated as P(B). 1.A-20 <B<A+20 2. P(B)×100 <P(A) The first point above excludes cases where the tip of peak A is broken or where there is a shoulder on peak A from being considered as peak B. Therefore, depending on the peak shape, it may be necessary to expand the exclusion range beyond the range of ±20 nm of A.
[0036] The second point above excludes noise from being considered as a peak of B. Therefore, depending on the noise level when measuring the wavelength dependence of the light intensity of each light source, even an intensity that is 1 / 100 or more of A may be considered as noise.
[0037] When there are two light sources, the "wavelength with the strongest intensity" for each light source is designated as the "wavelength with the strongest intensity (A)" and the "wavelength with the second strongest intensity (B)."
[0038] Similarly, even when there are three or more light sources, it is preferable that the in-plane retardation of the film is set to a common multiple of the "wavelengths having the strongest intensity" of the respective light sources.
[0039] In addition, even if the wavelength is not the "wavelength with the strongest intensity" for each light source, it is preferable to use a film with an in-plane retardation that is an integer multiple for a wavelength that plays an important role in the structure of the authentication device. The important role here is not limited to imaging for authentication, but also includes a role of influencing the target and causing a change, or eliminating the influence of anything other than the target.
[0040] There are no particular limitations on the method for setting the in-plane retardation of the film within the above range, but this can be achieved by adjusting the refractive index of the resin, the stretching ratio and the stretching temperature.
[0041] Examples of resins constituting the film of the present invention include polyesters such as polyethylene terephthalate (abbreviation: PET) and polyethylene naphthalate (abbreviation: PEN), polyethylene, polypropylene, cellophane, cellulose esters such as cellulose diacetate, cellulose triacetate (abbreviation: TAC), cellulose acetate butyrate, cellulose acetate propionate (abbreviation: CAP), cellulose acetate phthalate, and cellulose nitrate, and derivatives thereof, polyvinylidene chloride, polyvinyl alcohol, and polyethylene vinyl. Examples of such resins include alcohols, syndiotactic polystyrene, polycarbonate (abbreviation: PC), norbornene resins, polymethylpentene, polyether ketone, polyimide, polyether sulfone (abbreviation: PES), polyphenylene sulfide, polysulfones, polyether imide, polyether ketone imide, polyamide, fluororesin, nylon, polymethyl methacrylate, acrylics and polyarylates, and cycloolefin resins such as ARTON (registered trademark) (product name, manufactured by JSR Corporation) and APEL (registered trademark) (product name, manufactured by Mitsui Chemicals, Inc.).
[0042] Of these resins, films made of at least polyester are preferably used in terms of cost, availability, wide process window during film formation, and physical properties such as strength and elongation at break.
[0043] The polyester referred to in the present invention is a condensation polymer obtained by polymerization of a monomer mainly composed of an aromatic dicarboxylic acid or an aliphatic dicarboxylic acid and a diol. As a known industrial method for producing polyester, an ester exchange reaction (ester exchange method) or a direct esterification reaction (direct polymerization method) is used. Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid. Examples of aliphatic dicarboxylic acids include adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, 1,4-cyclohexanedicarboxylic acid, and ester derivatives thereof. Among them, terephthalic acid and 2,6-naphthalenedicarboxylic acid, which exhibit a high refractive index, are preferably used. As the dicarboxylic acid component, one of these may be used, or two or more of them may be used in combination.
[0044] Examples of the diol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbate, and spiroglycol. Among these, ethylene glycol is preferably used. These diol components may be used alone or in combination of two or more.
[0045] From the viewpoint of improving the film strength and stretchability, it is preferable that the laminated film is formed by alternately laminating five or more layers of a layer made of resin A and a layer made of a resin C different from resin A. Furthermore, it is preferable that resin A is mainly composed of crystalline resin A and resin C is mainly composed of amorphous resin C, from the viewpoint of facilitating the adjustment of the in-plane retardation. As the resin with a low refractive index, an amorphous resin whose refractive index is unlikely to increase during stretching can be used.
[0046] As the crystalline resin, for example, polyethylene terephthalate and its copolymers, polyethylene naphthalate and its copolymers, polybutylene terephthalate and its copolymers, polybutylene naphthalate and its copolymers, polyhexamethylene terephthalate and its copolymers, polyhexamethylene naphthalate and its copolymers, etc. can be used. In this case, as the copolymerization component, it is preferable that at least one of the above dicarboxylic acid components and at least one of the diol components are copolymerized.
[0047] Resins having a low refractive index are not particularly limited, and examples thereof include linear polyolefins such as polyethylene, polypropylene, poly(4-methylpentene-1), and polyacetal; alicyclic polyolefins which are obtained by ring-opening metathesis polymerization or addition polymerization of norbornenes, or addition copolymers with other olefins; biodegradable polymers such as polylactic acid and polybutyl succinate; polyamides such as nylon 6, nylon 11, nylon 12, and nylon 66; aramid, polymethyl methacrylate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl butyral, ethylene-vinyl acetate copolymer, and polyacetal. Polyesters such as polyglycolic acid, polystyrene, styrene copolymerized polymethyl methacrylate, polycarbonate, polypropylene terephthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate, polyethersulfone, polyetheretherketone, modified polyphenylene ether, polyphenylene sulfide, polyetherimide, polyimide, polyarylate, tetrafluoroethylene resin, trifluoroethylene resin, trifluorochloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, and polyvinylidene fluoride can be used. Among these, from the viewpoints of strength, heat resistance, transparency, and versatility, and particularly from the viewpoints of adhesion and lamination with crystalline resins, it is most preferable that resin C contains polyester as a constituent component. Here, the low refractive index resin may be a copolymer or a mixture.
[0048] For example, polyester containing isophthalic acid can reduce crystallinity, so that the in-plane retardation can be easily suppressed, and the refractive index in the thickness direction is not likely to decrease even when biaxially stretched, so that the occurrence of rainbow unevenness can be suppressed even if the angle of incidence of light from the light source changes. In addition, as another preferred amorphous polyester, polyester containing spiroglycol as a copolymerization component is preferred. Polyester containing spiroglycol is not likely to be oriented in film deformation due to biaxial stretching or bowing, so that in-plane retardation fluctuation in the width direction is unlikely to occur. In addition, since it has the effect of increasing the glass transition point, the increase in the thermal shrinkage rate due to the use of an amorphous resin can be suppressed. Other preferred copolymerized amorphous components include cyclohexanedimethanol, neopentyl glycol, cyclohexanedicarboxylic acid, isosorbide, etc.
[0049] The above film may be an unstretched film or a stretched film, but from the viewpoints of strength, in-plane retardation adjustment, and productivity, a film stretched in at least one direction is preferred. In particular, when the film of the authentication device is supported by a material that may break, such as glass, it is preferable to moderately stretch it to improve the elongation at break and prevent scattering of fragments due to surface damage. By increasing the stretching ratio in either the longitudinal direction or the width direction, the molecules in the film can be oriented and the in-plane retardation can be improved. By increasing the stretching ratio in the width direction, the in-plane retardation and the main orientation axis become uniform in the width direction, and the usable product width can be made large, which is preferable. When performing heat treatment after stretching to reduce the thermal shrinkage rate, it is preferable to further stretch in the width direction while performing heat treatment, to cool once before heat treatment, or to reduce the temperature difference between the temperature during stretching and the temperature during heat treatment, because the in-plane retardation and the main orientation axis can be made uniform in the width direction and the usable product width can be made large. In addition, lowering the stretching temperature makes it easier to achieve orientation during stretching, which can also improve the in-plane retardation. Conversely, if the temperature during stretching is increased, the molecules are stretched without being oriented, so the in-plane retardation is difficult to increase. In the present invention, it is necessary to adjust the stretching ratio and stretching temperature in order to make the in-plane retardation approximately an integer multiple of the light source wavelength. However, since the stretching ratio and stretching temperature greatly affect the physical properties that are important in using the film, such as the strength and elongation at break, it is difficult to achieve both the strength and elongation at break of the film and the target in-plane retardation. Therefore, as a method for adjusting the in-plane retardation, it is preferable to use a film in which two or more types of resins are alternately laminated in five or more layers. This is because, by adjusting the refractive index of the resin used in addition to the stretching ratio and stretching temperature, it becomes easier to design both the strength and elongation at break of the film and the in-plane retardation.
[0050] In addition, in the authentication device of the present invention, it is preferable that PT(0) and PT(45) measured by the following method satisfy the following formulas (III) and (IV). (III) PT(45) ≧ 0.65 (IV)1 ≧ PT(45) / PT(0)≧ 0.6 [Method of measuring PT(0) and PT(45)] (1) Measurements are performed using a spectrophotometer with a 50W tungsten lamp as a light source. (2) Cut the polarizer into two pieces and arrange them so that the faces of the two polarizers are perpendicular to the optical axis of the spectrophotometer and the transmission axes of the two polarizers are parallel to each other. (3) For the two polarizers, the amount of transmitted light at the wavelength with the strongest intensity of the light emitted from the light source is measured (background measurement). The amount of transmitted light obtained in the background measurement with the light source turned off is PT(D), and the amount of transmitted light with the light source turned on is PT(L). (4) The film is placed between two polarizers so that the film plane is perpendicular to the optical axis of the spectrophotometer. (5) While rotating only the film in a plane perpendicular to the optical axis of the spectrophotometer, the amount of transmitted light at the wavelength with the strongest intensity of the light emitted from the light source is measured. The amount of transmitted light when the angle between the transmission axes of the two polarizers and the main alignment axis of the film is 0° is designated as PT'(0), and the amount of transmitted light when the angle is 45° is designated as PT'(45). (6) PT(0) and PT(45) are obtained from the following equation. PT(0)=(PT'(0)- PT(D)) / (PT(L)- PT(D)) PT(45)=(PT'(45)- PT(D)) / (PT(L)- PT(D)) The PT(45) calculated above is understood to be the transmittance when the film is attached at an angle that is considered to be the lowest transmittance. Formula (III) indicates that the transmittance is preferably 0.65 or more even when the transmittance is at its lowest. If the transmittance is 0.65 or less, it may lead to a decrease in the authenticity.
[0051] The PT(0) obtained above represents the transmittance when the orientation angle is 0°, that is, the film is attached at an ideal angle from the viewpoint of improving transmittance. The ratio to PT(45), (PT(45) / PT(0)), represents the degree to which the transmittance decreases when the film is attached at a different angle from the ideal angle. If the ratio of PT(0) to PT(45) is not within the above range, that is, if PT(45) is larger than PT(0) or PT(45) is too small compared to PT(0), that is, if PT(45) / PT(0) is smaller than 0.6, in order to improve the authenticity of the authentication device, it is necessary to set the transmission axis of the polarizer and the main orientation axis of the film so that they are parallel, which may reduce productivity. More preferably, it is 0.75 or more and less than 1.0.
[0052] The film applicable to the present invention can be produced under specific film-forming conditions, although it is a conventionally known general film-forming method, as long as the refractive index, stretching ratio, and stretching temperature of the resin can be adjusted. For example, a substantially amorphous and unoriented unstretched film can be produced by melting the resin material with an extruder, extruding it with a circular die or a T-die, and quenching it. As described above, in order to achieve both the adjustment of the in-plane retardation and the improvement of the film strength, it is also preferable to laminate two or more types of resins. From the same viewpoint, it is particularly preferable to include a structure in which five or more layers of two types of resins are alternately laminated. Furthermore, a biaxially stretched film can be produced by stretching an unstretched film in the longitudinal direction of the film (transport direction, longitudinal axis direction, MD direction) or in a direction perpendicular to the longitudinal direction of the film (width direction, transverse axis direction, TD direction) by a known method such as uniaxial stretching, tenter-type sequential biaxial stretching, tenter-type simultaneous biaxial stretching, or tubular-type simultaneous biaxial stretching. In this case, the stretching ratio can be appropriately selected according to the resin used as the raw material of the film, but it is preferably within the range of 2 to 10 times in both the longitudinal and transverse directions. In order to suppress shrinkage during processing into an authentication device, it is also preferable to perform a heat treatment after stretching.
[0053] By forming the film within the above conditions, it is preferable that the elongation at break in both the main orientation axis direction and the direction perpendicular to the main orientation axis of the film at 25°C is 30% or more and 300% or less from the viewpoint of improving the handling property during processing and the strength of the film. It is more preferable that it is 50% or more and 200% or less. If the elongation at break is 30% or less, it is not preferable because it increases the possibility of breakage during processing and damage to the surface of the authentication device. In addition, if it exceeds 300%, it may lead to sagging during processing or a decrease in the strength of the film, which may lead to a decrease in authentication due to scratches and dents.
[0054] As described later, when the polarizer is installed in an authentication device, it is preferable that the transmission axis of the polarizer and the main orientation axis of the film are parallel from the viewpoint of transmittance and therefore authentication. Therefore, it is preferable that the direction of the main orientation axis of the film is constant in the MD direction and TD direction of the film. There is no particular limitation on the method for making the orientation angle constant, but for example, the stretching ratio in the MD direction or TD direction is made larger than the stretching ratio in the other direction, so that the ratio of the maximum value to the minimum value (maximum value / minimum value) of the heat shrinkage rate when treated at 100°C for 30 minutes in the main orientation axis direction and in the direction perpendicular to the main orientation axis is made to be a certain value or more. The ratio of the maximum value to the minimum value is preferably 1.7 or more, more preferably 2.0 or more, and even more preferably 3.0 or more.
[0055] The thickness of the film is preferably in the range of 3 to 200 μm, more preferably in the range of 10 to 150 μm, and particularly preferably in the range of 20 to 120 μm. By keeping the thickness within the above range, the thickness of the entire authentication device can be reduced while ensuring the strength required during processing.
[0056] In addition, the angle between the main orientation axis of the film and the transmission axis of the polarizer is preferably less than 10° from the viewpoint of suppressing a decrease in authenticity. If it exceeds 10°, the range of in-plane retardation with good authenticity becomes narrow, and the variation in in-plane retardation in the film plane may lead to a decrease in authenticity. However, during film production, a phenomenon called bowing described in JP 2010-240976 A occurs, so the range in which the orientation angle is uniform to an extent that it does not affect the authenticity is limited, and the range in which the orientation angle is not uniform results in production loss. In the film production conditions of the present invention, the longitudinal stretching ratio is 3.5 times or less and / or the transverse stretching ratio is 3.5 times or more, so that the direction of the main orientation axis becomes nearly constant over a wide width of the film, which is preferable from the viewpoint of productivity. It is more preferable to set the longitudinal stretching ratio to 3.2 times or less and / or the transverse stretching ratio to 4 times or more, and it is particularly preferable to set the longitudinal stretching ratio to 2.9 times or less and / or the transverse stretching ratio to 4.5 times or more. In addition, it is preferable to form a film having a multi-layer structure, since this makes it easier to suppress the change in the orientation angle in the width direction.
[0057] From the viewpoint of reducing unevenness in authentication, the above-mentioned film used in the authentication device of the present invention preferably has small unevenness in the in-plane retardation in the film plane. For example, an evaluation method of unevenness may be a method of measuring the in-plane retardation at a total of four points, namely, both ends (A, B) showing the maximum length in the film plane, and both ends (C, D) of the film of a straight line perpendicular to the straight line AB connecting points A and B and passing through the midpoint of the straight line AB. It is preferable that the difference between the maximum and minimum in-plane retardation values of the obtained four points is 200 nm or less. It is more preferable that the difference in the in-plane retardation is 150 nm or less, and particularly preferably 100 nm or less. In order to make the in-plane retardation within the above range, the method is not particularly limited, but it is preferable to stabilize the stress applied to the film as a whole by stretching the film by 2.7 times or more at once during film stretching.
[0058] In addition, in order to prevent deterioration of the internal polarizer and light source, it is preferable that the film blocks ultraviolet rays (here, light having a wavelength of 410 nm or less). When the light source is composed of an organic material such as an OLED, the ultraviolet ray blocking effect is particularly desired. It is most preferable to completely block light of 410 nm or less, but it is possible to prevent deterioration of the internal polarizer and light source by setting the light transmittance of the wavelength of 380 nm to 5% or less, for example. There is no particular limitation on the method of blocking ultraviolet rays, but it is preferable to reflect ultraviolet light by a multilayer structure. The setting of the reflection wavelength can be determined by the layer thickness of each layer of the multilayer laminate film, as described in JP 2016-215643 A. In addition to reflection, an ultraviolet ray absorber may be used, or may be used in combination with a reflection design.
[0059] As the ultraviolet absorbent that can be used in the present invention, it is preferable to use benzotriazole-based, benzophenone-based, benzoate-based, or triazine-based ones with a molecular weight of 300 g / mol or more. The ultraviolet absorbent may be selected from these, or two or more types may be used in combination. There is a relationship between the molecular weight and the sublimation property of additives such as ultraviolet absorbents, and when an additive with a large molecular weight is used, sublimation is unlikely to occur. The molecular weight is more preferably 400 g / mol or more, and even more preferably 500 g / mol or more. Many ultraviolet absorbents with a high molecular weight have a long alkyl chain attached to the basic aromatic ring skeleton, which is desirable because it inhibits stacking between ultraviolet absorbents and prevents problems such as crystallization in the resin causing an increase in haze.
[0060] The ultraviolet absorber that can be added is not particularly limited as a benzotriazole-based ultraviolet absorber, and examples thereof include 2-(2'-hydroxyphenyl)benzotriazoles such as 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-dicumylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-carboxyphenyl)benzotriazole, and 2,2'-methylenebis(4-tert-octyl-6-benzotriazolyl)phenol. Benzophenone-based ultraviolet absorbers are not particularly limited, but examples thereof include 2-hydroxybenzophenones such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, and 5,5'-methylenebis(2-hydroxy-4-methoxybenzophenone).
[0061] Benzoate-based ultraviolet absorbers include, but are not limited to, phenyl salicylate, resorcinol monobenzoate, 2,4-di-tert-butylphenyl-3,5-di-tert-butyl-4-hydroxybenzoate, 2,4-di-tert-amylphenyl-3,5-di-tert-butyl-4-hydroxybenzoate, hexadecyl-3,5-di-tert-butyl-4-hydroxybenzoate, and the like.
[0062] Examples of triazine-based ultraviolet absorbers include, but are not limited to, triaryltriazines such as 2-(2-hydroxy-4-octoxyphenyl)-4,6-bis(2,4-dimethylphenyl)-s-triazine, 2-(2-hydroxy-4-hexyloxyphenyl)-4,6-diphenyl-s-triazine, 2-(2-hydroxy-4-propoxy-5-methylphenyl)-4,6-bis(2,4-dimethylphenyl)-s-triazine, 2-(2-hydroxy-4-hexyloxyphenyl)-4,6-diviphenyl-s-triazine, 2,4-bis(2-hydroxy-4-octoxyphenyl)-6-(2,4-dimethylphenyl)-s-triazine, 2,4,6-tris(2-hydroxy-4-octoxyphenyl)-s-triazine, and 2-(4-isooctyloxycarbonylethoxyphenyl)-4,6-diphenyl-s-triazine.
[0063] Other UV absorbents that can be used include salicylic acid-based ones such as phenyl salicylate, t-butylphenyl salicylate, p-octylphenyl salicylate, etc., and others such as natural products (such as oryzanol, shea butter, baicalin, etc.) and biological systems (such as keratinocytes, melanin, urocanin, etc.). These UV absorbents can also be used in combination with hindered amine compounds as stabilizers. Inorganic UV absorbents are not preferred because they are not compatible with the base resin, leading to an increase in haze and worsening visibility when an image is displayed on an authentication device.
[0064] When an ultraviolet absorber is used, it may be added to layer A including the outermost layer of the laminated biaxially oriented film, which is a preferred embodiment of the present invention, or layer B which is the inner layer, or both. Of these, it is most preferable that the ultraviolet absorber is contained only in layer B. If an ultraviolet absorber is added to the outermost layer, the phenomenon that the added ultraviolet absorber precipitates on the film surface and the phenomenon that it volatilizes easily occurs, which is undesirable because it contaminates the film-making machine and the precipitate has a negative effect on the processing process. If it is added only to the inner layer, the outermost layer plays the role of a lid that prevents the ultraviolet absorber from volatilizing, so that the precipitation phenomenon is less likely to occur, which is preferable.
[0065] A coating may be applied to the film surface to impart functionality such as scratch resistance. The coating method is to use a curable resin as the main component, add a crosslinking agent such as melamine or oxazoline, and harden it with ultraviolet light.
[0066] The curable resin is preferably one that is highly transparent and durable, and for example, acrylic resin, urethane resin, fluorine resin, silicone resin, polycarbonate resin, vinyl chloride resin can be used alone or in combination. In particular, in terms of curability, flexibility, and productivity, the curable resin is preferably made of an active energy ray curable resin such as an acrylic resin represented by a polyacrylate resin. In addition, when adding scratch resistance during bending, which is required for a film applied to a portion requiring curved surface conformability, the curable resin is preferably made of a thermosetting urethane resin.
[0067] Furthermore, when the authentication device is intended to recognize the distribution pattern of melanin pigments present in the epidermis, for example, it is preferable that the light source wavelength is blue light (maximum peak wavelength is 415 nm or more and 495 nm or less) and the in-plane retardation of the film is in the range of an integer multiple of the light source wavelength to ±120 nm, that is, there exists an integer n that satisfies the following formula (V), in order to obtain a clear pattern, since melanin pigments strongly absorb ultraviolet to blue light. If the light source wavelength is shorter than 415 nm, there may be problems with erroneous authentication due to deterioration of the light source by ultraviolet light and large absorption by light other than melanin pigments. (V) A×n-120 ≦ Re ≦ A×n+120, and 415 ≦ A ≦ 495.
[0068] Furthermore, when the distribution pattern of hemoglobin is to be recognized, for example in vein authentication, since hemoglobin has a strong absorption peak in the infrared region, it is preferable that the light source wavelength is in the infrared region (maximum peak wavelength is 800 nm or more and 1200 nm or less) and the in-plane retardation of the film is in the range of an integer multiple of the light source wavelength to ±150 nm, that is, there is an integer n that satisfies the following formula (VIII), in order to obtain a clear pattern. Also, in the case of retina, iris, face authentication, etc., the subject of authentication looks directly at the light, so it may be preferable to use infrared rays in order to reduce discomfort to the subject of authentication. (VIII) A×n-150≦Re≦A×n+150, and 800≦A≦1200.
[0069] Similarly, depending on the color or design of the object to be authenticated, it may be preferable that the light source wavelength is green (maximum peak wavelength is 495 nm or more and 570 nm or less), i.e., there exists an integer n that satisfies the following formula (VI). Also, it may be preferable that the light source wavelength is yellow to red (maximum peak wavelength is 570 nm or more and 800 nm or less), i.e., there exists an integer n that satisfies the following formula (VII). (VI) A×n-100 ≦ Re ≦ A×n+100, and 495 ≦ A ≦ 570. (VII) A×n-120≦Re≦A×n+120, and 570≦A≦800.
[0070] Combining multiple of the above wavelengths is also effective for improving authentication accuracy, but in order to obtain the effects of the present invention, it is preferable to make the in-plane retardation of the film an approximately common multiple of the wavelengths of each light source being used, or to use films with different in-plane retardations for each light source.
[0071] The area of the authenticable region in the authentication device of the present invention is not particularly limited and is adjusted appropriately depending on the object to be authenticated and the purpose. Since the authentication device of the present invention uses a film having a uniform in-plane retardation and a uniform main alignment axis, the area of the authenticable region can be made large. That is, the authentication device of the present invention has an area of the authenticable region of 100 cm2. 2 More than that, even 225cm 2 More than 400cm 2 The present invention can be suitably used in the above devices.
[0072] As described above, the authentication device of the present invention can accurately recognize various authentication objects, and therefore can be suitably used as an authentication device that authenticates at least one of a fingerprint, an iris, a face, a handprint, a body shape, and veins. In addition, the authentication device of the present invention can provide good authentication accuracy even if the angle between the transmission axis of the polarizer and the main orientation axis of the film is large, thereby reducing the yield.
[0073] [Characteristics evaluation method] Film evaluation A. In-plane retardation (Re) and in-plane retardation difference (Δ retardation) The in-plane retardation and slow axis were measured at a wavelength of 587.8 nm at an incident angle of 0° using Oji Scientific Instruments' "KOBRA-21ADH". The direction of the slow axis was taken as the main alignment axis. Samples were cut out from the film at 5 different locations, measuring 4 cm x 4 cm, and the average value of each measurement was used.
[0074] The in-plane retardation unevenness was measured at a total of four points: the two ends (A, B) that showed the maximum length in the film plane, and the two ends (C, D) of the line that is perpendicular to the line AB connecting points A and B and passes through the midpoint of line AB. The difference between the maximum and minimum values was used to calculate the in-plane retardation unevenness.
[0075] B. PT(45) and PT(0) (1) Cut the polarizer used in the authentication device, or a polarizer with the same degree of polarization as the polarizer used (TS Wire Grid Polarizing Film (Edmund Optics Japan, Inc.)) into two pieces, and arrange them so that the faces of the two polarizers are perpendicular to the optical axis of a spectrophotometer using a 50W tungsten lamp as the light source, and the transmission axes of the two polarizers are parallel to each other, and perform background measurements with the light source off and with the light source on. The amount of transmitted light measured with the light source off is PT(D), and the amount of transmitted light measured with the light source on is PT(L). (2) The film is placed between two polarizers so that the film plane is perpendicular to the optical axis of the spectrophotometer. (3) While rotating only the film in a plane perpendicular to the optical axis of the spectrophotometer, the amount of transmitted light at the wavelength with the strongest intensity of the light emitted from the light source is measured. The amount of transmitted light when the angle between the transmission axes of the two polarizers and the main orientation axis of the film is 0° is defined as PT'(0), and the amount of transmitted light when the angle is 45° is defined as PT'(45). (4) PT(0) and PT(45) are obtained from the following equation. PT(0)=(PT'(0)- PT(D)) / (PT(L)- PT(D)) PT(45)=(PT'(45)- PT(D)) / (PT(L)- PT(D)) C. Light source transmittance and 380 nm transmittance The transmittance at an incident angle of 0° was measured using a spectrophotometer (U-4100 Spectrophotometer) manufactured by Hitachi High-Technologies Corporation. Measurement conditions: the slit was set to 2 nm, the gain was set to 2, and the scanning speed was set to 600 nm / min. Samples were cut out from the film at 5 different locations x 4 cm x 4 cm, and the average value of the measurements was used.
[0076] The reflector of the integrating sphere was made of aluminum oxide, the photometry method was double-beam direct ratio photometry, and the spectrometer was a prism and grating-grating type double monochromator.
[0077] The light source light transmittance refers to the transmittance at the wavelength at which the light emitted from the light source of the authentication device has the strongest intensity.
[0078] D. Elongation at break The film was cut out from the center of the sample width to a width of 10 mm x 150 mm. Measurements were performed in accordance with JIS-C-2151 and ASTM-D-882 using a digital micrometer (HKT-1208 manufactured by Matsuo Sangyo) and a tensile tester (RTG1210). The sample was held in a chuck in the direction of the main orientation axis and pulled at a speed of 200 mm / min to determine the strength (tensile load value divided by the cross-sectional area of the test piece) and elongation when the sample broke (fractured). Tensile elongation was calculated using the following formula. Tensile elongation (%) = 100 × (L-Lo) / Lo Lo: sample length before test L: sample length at break The measurement was carried out five times, and the average value was used. Similarly, the elongation at break in the direction perpendicular to the main orientation axis was also measured. The measurement was carried out in a room maintained at 25°C.
[0079] E. Light source wavelength and light source half-width The light from the light source was measured using a Hamamatsu Photonics mini spectrophotometer (C10083MD, C9914GB) equipped with an optical fiber with a numerical aperture of 0.22. The wavelength with the highest intensity in the range of 320 nm to 1500 nm was defined as the light source wavelength, and the width of the peak at half the intensity of the peak intensity of the light source wavelength was defined as the half-width.
[0080] F. Thickness Using a digital micrometer (HKT-1208 manufactured by Matsuo Sangyo), the central part of the film was measured in accordance with JIS-C-2151. The measurement was carried out three times, and the average value was used.
[0081] Authentication Device Evaluation G. Authenticity An authentication object α is registered in an environment of 23°C and 65% RH. In the case of Example 10, the iris is used as the authentication object, and in other cases, a fingerprint is used. After that, the authentication object α and an unregistered authentication object β are alternately recognized by the authentication device 200 times each. The recognition time is 2 seconds each. The probability of rejecting α (false rejection rate: FRR) and the probability of accepting β (false acceptance rate: FAR) are evaluated as follows: A is good, B is fair, and C and D are unsuitable. A:FRR≦1.0%,FAR≦0.5% B: 1.0% <FRR≦3.0%、FAR≦0.5% C: 3.0% <FRR≦5.0%もしくは / かつ、0.5%<FAR≦1.0% D: 5.0% <FRRもしくは、1.0%<FAR。
[0082] H.Light source durability The authentication device was kept in an atmosphere of 23°C and 65% RH with the light source turned on for 1000 hours, and the change in authentication performance before and after the test was evaluated. The criteria for evaluation are as follows. However, ΔFRR and ΔFAR respectively indicate the values obtained by subtracting the FRR and FAR before the test from the FRR and FAR after the test. A: ΔFRR = 0 and ΔFAR = 0. B: "0<ΔFRR≦1.0 and 0<ΔFAR≦0.5" C: "1.0<ΔFRR≦2.0 and 0<ΔFAR≦0.5", "0<ΔFRR≦1.0 and 0.5<ΔFAR≦1.5" or "1.0<ΔFRR≦2.0 and 0.5<ΔFAR≦1.5" D: None of A, B, or C apply.
[0083] I. Impact durability The impact value was measured using a film impact tester (manufactured by Toyo Seiki Seisakusho) with a hemispherical impact head having a diameter of 1 / 2 inch, in an atmosphere of 23°C temperature and 65% RH. Five measurements were made for each sample. Furthermore, the impact value for each measurement was divided by the thickness of the film attached to the measured sample to obtain the impact value per unit thickness, and the average value of the five measurements was calculated. The measured values were evaluated as follows: A:1.0N m / mm or more B: 0.5N·m / mm or more and less than 1.0N·m / mm C: Less than 0.5 N·m / mm.
[0084] J: Heat shrinkage rate Five samples with a width of 10 mm and a length of 200 mm (measurement direction) were cut out for each of the MD and TD directions of the film, and a mark was made 25 mm from each end as a benchmark, and the distance between the benchmark was measured with a universal projector to obtain the test length (10). Next, the test pieces were sandwiched between paper and heated for 30 minutes in an oven kept at 100°C with no load, and then removed and cooled at room temperature. The dimension (11) was measured with a universal projector and calculated using the following formula, and the average of the five pieces was taken as the thermal shrinkage rate. Heat shrinkage rate = {(10-11) / 10} x 100(%) EXAMPLES
[0085] The present invention will be described below with reference to examples, but the present invention is not necessarily limited to these. Note that Examples 13 and 14 are currently Reference Examples 1 and 2.
[0086] Example 1 The light source and light sensitivity sensor used were ClearID FS9500 manufactured by Synaptics (light source wavelength: 525 nm, light source half-width: 30 nm). The polarizer used was a general polarizing film with a polarization degree of 80% or more, VF-PS#7500 manufactured by Kuraray Co., Ltd. The film was prepared in the following manner.
[0087] (Resin used to create the film) Resin A: Polyethylene terephthalate (PET) (intrinsic viscosity: 0.65) Resin B: Polyethylene terephthalate copolymerized with 25 mol% spiroglycol based on the total diol component and 30 mol% cyclohexanedicarboxylic acid based on the total dicarboxylic acid component (PET / SPG / CHDC) (intrinsic viscosity: 0.72) Resin C: Resin B (90% by weight) and the ultraviolet absorber 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol] (10% by weight) were mixed using an extruder and pelletized. Resin D: Resin A (90% by weight) and the ultraviolet absorber 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol] (10% by weight) were mixed using an extruder and pelletized. Resin E: Polyethylene terephthalate (PET) (intrinsic viscosity: 0.65) containing 0.8% by weight of divinylbenzene / styrene copolymer particles with an average particle size of 0.70 μm and 1.5% by weight of agglomerated alumina particles with an average secondary particle size of 0.08 μm.
[0088] (Film Creation) Resin A was used as the resin constituting layer A, and resin C was used as the resin constituting layer B. The intrinsic viscosity of resin C was 0.72, and the in-plane average refractive index after filming was 1.55. Thermoplastic resin A and thermoplastic resin C were melted at 280°C in an extruder, respectively, and passed through five FSS-type leaf disk filters, and then alternately merged in a 201-layer feed block (101 layers of layer A and 100 layers of layer B) while being measured so that the discharge ratio (lamination ratio) was resin A / resin C = 1.5 / 1 by a gear pump and the film thickness after biaxial stretching was 35 μm. Next, the mixture was fed to a T-die and formed into a sheet, and then quenched and solidified on a casting drum whose surface temperature was kept at 25°C while applying an electrostatic voltage of 8 kV with a wire, to obtain an unstretched multilayer laminate film. Sequential biaxial stretching was performed on this unstretched film. First, the film was transported on a Teflon (registered trademark) roll at 105°C, and then stretched 2.8 times at 95°C in the longitudinal direction while being heated by an infrared heater with an output of 500W to obtain a uniaxially stretched film. This uniaxially stretched film was stretched 4.5 times in the width direction at 100°C in a tenter, and then heat-set at 220°C, during which it was relaxed by 1.7% in the width direction and cooled in the transport process, after which the edges were cut and the film was wound up to obtain a film. The physical properties of the obtained film are shown in Tables 1 and 3.
[0089] (Creating an authentication device) The ClearID (light source, photosensitivity sensor), polarizer, and film were adhered in that order using an optically clear adhesive (OCA: Optically Clear Adhesive) to obtain an authentication device. The main orientation axis of the film was arranged parallel to the transmission axis of the polarizer. The authentication area of the authentication device was 1 cm. 2 The characteristics of the obtained authentication device are shown in Tables 2 and 4. An authentication device with excellent authentication capability and durability was obtained.
[0090] Example 2 An authentication device was obtained in the same manner as in Example 1, except that the main orientation axis of the film attached to the device was set at 45° to the transmission axis of the polarizer. As shown in Table 2, an authentication device with excellent authentication properties and durability was obtained.
[0091] Example 3 A film and an authentication device were obtained in the same manner as in Example 2, except that the stretching ratio in the width direction was 5.5 times. An authentication device having excellent authentication properties and durability was obtained.
[0092] Example 4 Except for changing the longitudinal stretching ratio to 3.0 times, a film and an authentication device were obtained in the same manner as in Example 1. An authentication device having excellent authentication properties and durability was obtained.
[0093] Example 5 An authentication device was obtained in the same manner as in Example 4, except that the main orientation axis of the film was set at 10° to the transmission axis of the polarizer. An authentication device having good authentication properties and excellent durability was obtained.
[0094] Example 6 An authentication device was obtained in the same manner as in Example 4, except that the main orientation axis of the film was set at 45° to the transmission axis of the polarizer. An authentication device having good authentication properties and excellent durability was obtained.
[0095] Example 7 A film and an authentication device were obtained in the same manner as in Example 2, except that the longitudinal stretching ratio was 2.6 times. An authentication device having good authentication properties and excellent durability was obtained.
[0096] Example 8 A film and an authentication device were obtained in the same manner as in Example 2, except that Resin D was used as the resin constituting Layer B. An authentication device having good authenticity and durability was obtained.
[0097] Example 9 A film and an authentication device were obtained in the same manner as in Example 2, except that the temperature during longitudinal stretching was 90° C. and the temperature during widthwise stretching was 120° C. An authentication device with good authentication properties and excellent durability was obtained.
[0098] Example 10 A film and an authentication device were obtained in the same manner as in Example 2, except that Panasonic BM ET-200 was used as the light source and the light sensitivity sensor instead of ClearID, and the longitudinal stretching ratio was set to 3.2 times. An authentication device with excellent authentication properties and durability was obtained.
[0099] Example 11 A film and an authentication device were obtained in the same manner as in Example 2, except that a three-layer feedblock (two outer layers of A layer and one inner layer of B layer) was used. The resulting authentication device had excellent authentication properties.
[0100] Example 12 A film and an authentication device were obtained in the same manner as in Example 2, except that Resin B was used as the resin constituting Layer B. The authentication device had excellent authentication properties.
[0101] (Example 13) A film and an authentication device were obtained in the same manner as in Example 2, except that the stretching ratio in the longitudinal direction was 1.05 times and the stretching ratio in the transverse direction was 1.05 times and heat treatment was not performed. The authentication device had excellent authentication properties.
[0102] Example 14 A film and an authentication device were obtained in the same manner as in Example 2, except that a polycarbonate film (Teijin Panlite PC-7129) was used as the film. The authentication device had excellent authentication properties.
[0103] Example 15 Authentication area is 50cm 2 Except for the above, an authentication device was obtained in the same manner as in Example 1. The authentication device had excellent authentication properties.
[0104] (Example 16) A film and an authentication device were obtained in the same manner as in Example 15, except that the stretching ratio in the longitudinal direction was 4.2 times and the stretching ratio in the transverse direction was 2.3 times. The authentication device had good authentication properties.
[0105] (Example 17) A film and an authentication device were obtained in the same manner as in Example 1, except that the stretching ratio in the width direction was 4.4 times. When measuring the in-plane retardation of this film, the light source wavelength was set to 587.8 nm, and also the light source wavelength was set to 525 nm using a color filter. The results measured at 525 nm are shown in parentheses in the Re (nm) column in Table 3. As shown in Table 4, the authentication device had particularly excellent authenticity with FRR = 0% in the authenticity test.
[0106] (Example 18) A film and an authentication device were obtained in the same manner as in Example 2, except that the stretching ratio in the width direction was 4.4 times. When measuring the in-plane retardation of this film, the light source wavelength was set to 587.8 nm, and also the light source wavelength was set to 525 nm using a color filter. The results measured at 525 nm are shown in parentheses in the Re (nm) column in Table 3. As shown in Table 4, the authentication device had particularly excellent authenticity with FRR = 0% in the authenticity test.
[0107] (Example 19) An authentication device was obtained in the same manner as in Example 2, except that the light source and light sensitivity sensor of ClearID and the light source and light sensitivity sensor of BM ET-200 were used simultaneously. ClearID had a higher light intensity from the light source than BM ET-200. The authentication device had excellent authentication performance only from the data from the light sensitivity sensor of ClearID. For the measurement items in Tables 3 and 4 that require a light source wavelength for measurement, the measurement results at 525 nm are listed outside parentheses, and the results at 850 nm are listed inside parentheses.
[0108] (Example 20) A film and an authentication device were obtained in the same manner as in Example 19, except that the stretching ratio in the width direction was 5.7 times. ClearID had a higher light intensity from the light source than BM ET-200. The data from both the ClearID light sensitivity sensor and the BM ET-200 light sensitivity sensor showed that the authentication device had excellent authentication properties. For the measurement items in Tables 3 and 4 that require a light source wavelength for measurement, the measurement results at 525 nm are listed outside parentheses, and the results at 850 nm are listed inside parentheses.
[0109] Example 21 A film and an authentication device were obtained in the same manner as in Example 5, except that the heat treatment temperature was 240° C. As shown in Table 4, the authentication device had good authentication properties.
[0110] Example 22 A film and an authentication device were obtained in the same manner as in Example 2, except that the stretching ratio in the longitudinal direction was 2.6 times and the stretching ratio in the transverse direction was 4.0 times. As shown in Table 4, although the variation in the in-plane retardation was somewhat large, the authentication device had good authentication properties overall.
[0111] (Example 23) A film and an authentication device were obtained in the same manner as in Example 5, except that Resin E was used instead of Resin A. As shown in Table 4, an authentication device with good authentication properties was obtained.
[0112] Example 24 A film and an authentication device were obtained in the same manner as in Example 2, except that a 9-layer feedblock (5 outer A layers and 4 inner B layers) was used. As shown in Table 4, an authentication device with excellent authentication properties was obtained.
[0113] (Example 25) A film and authentication device were obtained in the same manner as in Example 2, except that a 101-layer feedblock (51 outer A layers and 50 inner B layers) was used and the extrusion rate was adjusted to a thickness of 18 μm after stretching. Although the impact resistance was slightly reduced by reducing the thickness, the film was applicable to applications requiring a thin film. As shown in Table 4, an authentication device with excellent authentication properties was obtained.
[0114] Comparative Example 1 A film and an authentication device were obtained in the same manner as in Example 2, except that the stretching ratio in the longitudinal direction was set to 3.2 times and the main alignment axis of the film was set to 10° with respect to the transmission axis of the polarizer. The authentication device had slightly inferior authentication properties.
[0115] Comparative Example 2 A film and an authentication device were obtained in the same manner as in Example 2, except that the stretching ratio in the longitudinal direction was 3.2 times. The authentication device had poor authentication properties.
[0116] Comparative Example 3 A film and an authentication device were obtained in the same manner as in Example 2, except that the stretching ratio in the width direction was 4.9 times. The authentication device had poor authentication properties.
[0117] Comparative Example 4 A film and an authentication device were obtained in the same manner as in Comparative Example 2, except that the stretching ratio in the longitudinal direction was 3.2 times and the stretching ratio in the transverse direction was 4.4 times. The authentication device had poor authentication properties.
[0118] [Table 1]
[0119] [Table 2]
[0120] [Table 3]
[0121] [Table 4] [Industrial Applicability]
[0122] The authentication device of the present invention has an authentication performance that is not dependent on the orientation angle of the film, and the durability of the light source and polarizer is improved by the film absorbing and reflecting ultraviolet light, and the film can be made of inexpensive polyester, so that the device has good authentication performance and durability, is inexpensive, and has excellent productivity. [Explanation of symbols]
[0123] 1:Light source 2: Polarizer 3:Film 4: Light sensitivity sensor 5: Light emitted from a light source and reflected by an object to be authenticated 6: Light emitted from the light source
Claims
1. An authentication device having a light source, a polarizer, a film, and a light sensitivity sensor for authenticating at least one of a fingerprint, an iris, a face, a handprint, a body shape, and a vein, wherein the film is placed between the polarizer and an object to be authenticated, and the authentication device satisfies the following (1) to (5). (1) The transmittance of the light beam emitted from the light source is 70% or more and 100% or less at the wavelength at which the light beam has the strongest intensity. (2) There exists an integer n that satisfies the following formula (I): (I) A×n-150 ≦ Re ≦ A×n+150 Here, A is the wavelength (nm) at which the light emitted from the light source has the strongest intensity, Re is the in-plane retardation (nm) of the film measured at a wavelength of 587.8 nm and an incident angle of 0° using the parallel Nicol rotation method. (3) The in-plane retardation of the film is 400 nm or more and 3,000 nm or less. (4) The film has an elongation at break at 25° C. in both the main orientation axis direction and the direction perpendicular to the main orientation axis of 30% or more and 300% or less. (5) The half-width of the peak exhibiting the strongest intensity in the light beam emitted from the light source is 5 nm or more and 70 nm or less.
2. The authentication device according to claim 1 , wherein there exists an integer m that satisfies the formula (I) and also satisfies the following formula (II): (II) B×m-150 ≦ Re ≦ B×m+150 Here, B is the wavelength (nm) exhibiting the second strongest intensity in the light beam emitted from the light source, Re is the in-plane retardation (nm) of the film measured at a wavelength of 587.8 nm and an incident angle of 0° using the parallel Nicol rotation method.
3. The authentication device according to claim 1 or 2, wherein the film satisfies the following formulas (III) and (IV). (III) PT(45) ≧ 0.65 (IV) 1 ≧ PT (45) / PT (0) ≧ 0.6 Here, PT(45) and PT(0) are calculated as follows. (1) Cut a polarizer into two pieces, and arrange them so that the surfaces of the two polarizers are perpendicular to the optical axis of a spectrophotometer using a 50 W tungsten lamp as the light source and the transmission axes of the two polarizers are parallel to each other, and perform background measurements with the light source turned off and on. The amount of transmitted light measured with the light source turned off is designated as PT(D), and the amount of transmitted light measured with the light source turned on is designated as PT(L). (2) The film is placed between two polarizers so that the plane of the film is perpendicular to the optical axis of the spectrophotometer. (3) While rotating only the film in a plane perpendicular to the optical axis of the spectrophotometer, the amount of transmitted light at the wavelength having the strongest intensity of the light emitted from the light source is measured. The amount of transmitted light when the angle between the transmission axes of the two polarizers and the main alignment axis of the film is 0° is defined as PT'(0), and the amount of transmitted light when the angle is 45° is defined as PT'(45). (4) PT(0) and PT(45) are obtained from the following formula. PT(0) = (PT'(0) - PT(D)) / (PT(L) - PT(D)) PT(45) = (PT'(45) - PT(D)) / (PT(L) - PT(D)).
4. 4. The authentication device according to claim 1, wherein an integer n exists that satisfies the following formula (V): (V) A×n-120≦Re≦A×n+120, and 415≦A≦495.
5. 4. The authentication device according to claim 1, wherein an integer n exists that satisfies the following formula (VI): (VI) A×n−100≦Re≦A×n+100, and 495≦A≦570.
6. 4. The authentication device according to claim 1, wherein an integer n exists that satisfies the following formula (VII): (VII) A×n−120≦Re≦A×n+120, and 570≦A≦800.
7. 4. An authentication device according to claim 1, wherein there exists an integer n that satisfies the following formula (VIII): (VIII) A×n−150≦Re≦A×n+150, and 800≦A≦1600.
8. 8. The authentication device according to claim 1, wherein the film is a laminated film in which layers of resin A and layers of resin C different from resin A are alternately laminated in five or more layers.
9. The authentication device described in claim 8, characterized in that the resin C constituting the film contains at least one of cyclohexanedimethanol, spiroglycol, neopentyl glycol, isophthalic acid, cyclohexanedicarboxylic acid, and isosorbide, and is mainly composed of polyester.
10. An authentication device described in any one of claims 1 to 9, wherein the ratio of maximum to minimum thermal shrinkage rates (maximum value / minimum value) when treated for 30 minutes at 100°C in the main orientation axis direction and in a direction perpendicular to the main orientation axis of the film is 1.7 or more.
11. The authentication device according to claim 1 , wherein the angle between the main orientation axis of the film and the transmission axis of the polarizer is less than 10°.
12. The authentication device according to any one of claims 1 to 11, wherein the difference between the maximum and minimum in-plane retardation at a total of four points, namely, both ends (A, B) showing the maximum length in the film plane, and both ends (C, D) of the film on a line that is perpendicular to the line AB connecting points A and B and passes through the midpoint of the line AB, is 200 nm or less.
13. The area of the area that can be authenticated is 10 cm 2 The authentication device according to any one of claims 1 to 12.
14. The authentication device according to any one of claims 1 to 13, wherein the light source includes either an organic electroluminescence element (EL) or a light-emitting diode (LED), and the light transmittance of the film at a wavelength of 380 nm is 5% or less.
15. The authentication device according to any one of claims 1 to 14, wherein the light-sensitive sensor is a complementary metal-oxide-semiconductor (CMOS) sensor.
Citation Information
Patent Citations
Polyester film for lamination with polarizing film
JP2002040249A
Release film
JP2003231214A
Polarizing reflector
JP2011118190A
Optical filter and image capturing device using the same
JP2018189725A
Optical filter
JP2018194620A